Influence of post-bleaching time on enamel bond strength - Alvarez, Nilda María del Rosario (2021)
The time interval after tooth bleaching is a significant variable for the adhesion to the tooth structure. The bleaching agents used on the enamel surface, due to the degradation of the peroxides used, generate oxygen free radicals that alter the bonding strength. The literature has shown conclusively that the time that has elapsed since a bleaching to the moment of restoration is decisive for the adhesion to the enamel. The objective of this work was to review the literature about the influence of time after dental bleaching and its effect on the strength of adhesion to enamel of composite resins. Data collection was carried out through electronic databases such as: Scielo, EBSCO, academic repositories, obtaining 36 articles and thesis. After the analysis, it can be considered that time is decisive in the adhesive resistance and that the alterations after tooth bleaching extend until the subsequent week, lasting up to four weeks, a time that the literature considers necessary for the elimination of residual oxygen.